Association Between Prelacteal Feeding and Infant Growth. (29th May 2020) - Tong, Hanzhi; Thorne-Lyman, Andrew; Palmer, Amanda; Shaikh, Saijuddin; Ali, Hasmot; Gao, Ya; Pasqualino, Monica; Wu, Lee; Alland, Kelsey; Schulze, Kerry; West, Keith; Hossain, Md Iqbal; et al.
Abstract: Objectives: To assess the association between exposure to prelacteal feeding and infant growth from birth to 3 months of age. Methods: We analyzed data from a cohort of mothers and infants ( n  = 2569) identified as part of ongoing pregnancy and birth surveillance in rural Gaibandha, Bangladesh. Trained interviewers visited women in their households during pregnancy to collect sociodemographic data. Project staff were notified of a birth by telephone and interviewers visited the home within three days post-partum, at one-week, and at three months. At each visit, interviewers collected detailed data on breastfeeding, any foods provided to the infant other than breast milk, and morbidity. Infant weight, length, and mid-upper arm circumference were measured according to standardized protocols at birth and three months of age. For analysis, we defined exposure to prelacteal feeding (PLF) as giving infants any food or liquid other than breastmilk within first 3 days of life. Infant length and weight measurements were used to produce length-for-age (LAZ), weight-for-age (WAZ), and weight-for-length (WLZ) Z-scores. Stunting, wasting, and underweight were defined as a LAZ, WLZ, or WAZ < −2, respectively. We used multiple linear regression and multiple logistic regression to assess the association between anthropometric indices and PLF practices, controlling for low birthweight, infant sex, infant age, maternal education, maternal age, and wealth. Results: The prevalence of PLF was 25.2%. The prevalence of stunting, wasting and underweight was 29.0%, 3.8% and 22.3%, respectively. For stunting (adjusted risk ratio (ARR) = 1.02 [95% CI: 0.89–1.16]) and wasting (ARR = 0.97 [95% CI: 0.63–1.50]), there were no differences between infants who received PLF and infants who did not receive any PLF. Infants who received PLF tended to have higher risk of underweight (ARR = 1.10 [95% CI: 0.95–1.28]). For LAZ, WAZ, and WLZ score, no differences were observed in the adjusted analysis between infants who received PLF and those who did not receive any PLF. Conclusions: There was no association between exposure to PLF and infant growth from birth to 3 months of age. More research is needed to explore the potential effect of PLF on other outcomes. Funding Sources: Bill & Melinda Gates Foundation; Johnson & Johnson; UBS Optimus Foundation.